2021
DOI: 10.1007/s13311-020-00972-w
|View full text |Cite|
|
Sign up to set email alerts
|

Deferiprone Treatment in Aged Transgenic Tau Mice Improves Y-Maze Performance and Alters Tau Pathology

Abstract: The accumulation of neurofibrillary tangles (NFTs), which is composed of abnormally hyperphosphorylated tau aggregates, is the classic neuropathology associated with cognitive dysfunction in tauopathies such as Alzheimer's disease (AD). However, there is an emerging theory suggesting that dysregulation in cerebral iron may contribute to NFT formation. Iron is speculated to bind to tau and induce conformational changes of the protein, potentially leading to subsequent aggregation and cognitive decline. Deferipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…Using tau‐overexpressing transgenic mice (rTg4510), deferiprone improved locomotor and memory (Y‐maze) function and attenuated anxiety‐like behaviour in the open‐field test (Rao et al, 2021). An accompanied 28% reduction in brain iron levels was seen, and decreased hippocampal ferritin and phosphorylated tau (Rao et al, 2021). These behavioural and iron‐related changes are consistent with our findings albeit in TBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using tau‐overexpressing transgenic mice (rTg4510), deferiprone improved locomotor and memory (Y‐maze) function and attenuated anxiety‐like behaviour in the open‐field test (Rao et al, 2021). An accompanied 28% reduction in brain iron levels was seen, and decreased hippocampal ferritin and phosphorylated tau (Rao et al, 2021). These behavioural and iron‐related changes are consistent with our findings albeit in TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Short‐term working memory was examined using the Y‐maze, as described previously (Portbury, Hare, Finkelstein, & Adlard, 2017; Rao et al, 2021). The Y‐maze consists of two familiar arms and one novel arm with visual cues along the walls of each arm of the maze.…”
Section: Methodsmentioning
confidence: 99%
“…We also revealed an anxiogenic-like effect of acute deferiprone in both genotypes. In a mouse model of tauopathy, Rao et al [67] found that chronic deferiprone treatment had an anxiolytic-like effect. However, this was in a model of tauopathy following 16 weeks of treatment and using time spent in the outer arena zone as a measure of anxietylike behaviours, which was substantially different from our acute study.…”
Section: Antidepressant-like Effects Of Deferipronementioning
confidence: 99%
“…This chelator is likely to act intracellularly [385]. Experimentally, deferiprone has been shown to mobilize Fe deposited in brain [386].…”
Section: Iron Chelation and Other Means To Decrease Cerebral Ironmentioning
confidence: 99%